Energetic potential of eucalyptus clones wood in different planting spacing (Research, Society and Development, 2020)
Aiming to evaluate the potential wood energy of three clones of eucalyptus in different planting spacings, was installed an experiment with a randomized block design in a factorial design, with a combination of six spacings (2,5 x 0,5 m; 2,5 x 1,0 m; 2,5 x 2,0 m; 3,0 x 0,5 m; 3,0 x 1,0 m e 3,0 x 2,0 m) three eucalyptus clones (GG 157, GG 680 e GG 100), with three replicates. At 32 months old, was selected and cut down a medium-diameter tree per plot. These trees were scaled by Smalian method, using sections from 2.0 m to DAP. On these sections were removed wooden disks with 5.0 cm thick, which were used for the analyzes of basic density and calorific value of wood and, based on these values, it was possible to estimate the amount of energy stored per m³. It was observed that the basic density of wood, the gross calorific power and the energy stored in eucalyptus wood were different with the clones and planting spacing. Basic density and the amount of energy stored in a cubic meter of eucalyptus wood tended to increase with in the planting spacing, mainly for GG 680 and GG100 clones. The superior gross calorific of the wood showed no direct relationship with the planting density.